FIRST REPORT OF HYPODERAEUM CONOIDEUM INFECTION IN FREE RANGING DUCK FLOCK IN TAMIL NADU - V. Gowthaman; C. Soundararajan; T.R. Gopala Krishna Murthy; A. Komathi (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Six adult dead ducks from neighbouring area of Namakkal district were brought for post-mortem examination with a history of chronic debility, morbidity and mortality to Poultry Disease Diagnosis and Surveillance Laboratory, Namakkal, Tamil Nadu. Post mortem examination of carcasses revealed that flatworms were attached to the lining of the mucosal epithelium and obstructing gastro intestinal tract indicative of verminous enteritis. The flukes were identified as Hypoderaeum conoideum. The parasitological studies revealed that H. conoideum was the cause of verminous enteritis in the affected flock.